Evidence of Avian Leukosis Virus Subgroup E and Endogenous Avian Virus in Measles and Mumps Vaccines Derived from Chicken Cells: Investigation of Transmission to Vaccine Recipients - Tsang, Shirley X. (American Society for Microbiology, 1999)
Reverse transcriptase (RT) activity has been detected recently in all chicken cell-derived measles and mumps vaccines. A study of a vaccine manufactured in Europe indicated that the RT is associated with particles containing endogenous avian retrovirus (EAV-0) RNA and originates from the chicken embryonic fibroblasts (CEF) used as a substrate for propagation of the vaccine. We investigated the origin of RT in measles and mumps vaccines from a U.S. manufacturer and confirm the presence of RT and EAV RNA. Additionally, we provide new evidence for the presence of avian leukosis virus (ALV) in both CEF supernatants and vaccines. ALV pol sequences were first identified in particle-associated RNA by amplification with degenerate retroviral pol primers. ALV RNA sequences from both the gag and env regions were also detected. Analysis of hypervariable region 2 of env revealed a subgroup E sequence, an endogenous-type ALV. Both CEF- and vaccine-derived RT activity could be blocked by antibodies to ALV RT. Release of ALV-like virus particles from uninoculated CEF was also documented by electron microscopy. Nonetheless, infectivity studies on susceptible 15B(1) chicken cells gave no evidence of infectious ALV, which is consistent with the phenotypes of the ev loci identified in the CEF. PCR analysis of ALV and EAV proviral sequences in peripheral blood mononuclear cells from 33 children after measles and mumps vaccination yielded negative results. Our data indicate that the sources of RT activity in all RT-positive measles and mumps vaccines may not be similar and depend on the particular endogenous retroviral loci present in the chicken cell substrate used. The present data do not support transmission of either ALV or EAV to recipients of the U.S.-made vaccine and provide reassurance for current immunization policies.